Synthesis and Spectral Properties of Cd(II), Pb(II) and Bi(III) Complexes of Furan-2-Aldoxime and Thiopene-2-Aldoxime - Mehta, B.H.; Balsaraf, V.M. (Asian Journal of Chemistry, 2010)
The furan-2-aldoxime and thiopene-2-aldoxime were used to prepare Cd(II), Pb(II) and Bi(II) complexes by two different methods. The crystalline products were characterized by analytical parameters witch suggest the molecular stoichiometry as M(L)n where n = 2 for Cd(II) and Pb(II) while n = 3 for Bi(III) complexes for precipitation method while refluxion method gave complexes with formula MCl2(L)2 where M = Cd(II) or Bi(III). Each of these complexes was characterised by IR spectral data.